Adsorption and Desorption of Reactive Dyes onto Chitin and Chitosan Flakes and Beads - Urszula Filipkowska (Adsorption Science & Technology)
A study was undertaken to analyze the adsorption and desorption of four Reactive dyes, i.e. Reactive Yellow 84 (RY 84), Reactive Red 11 (RR 11), Reactive Black 5 (RB 5) and Reactive Black 8 (RB 8), onto chitin (sorbent 1) and chitosan in the form of flakes (sorbent 2) and beads (sorbent 3). The maximum adsorption capacity of sorbents 1, 2 and 3 and the quantity of desorbed dye were determined for the four dyes and the three types of sorbent examined. For all the Reactive dyes, the adsorption capacities of sorbents 2 and 3 were higher than that of sorbent 1, with the desorption efficiency being lower than the efficiency of the adsorption process. The highest efficiency of dye release, ca. 90%, was obtained for sorbent 1 and the chlorotriazine dyes.